Optimization of Writing Skills through the Jolly Phonics Method: An Innovative Approach in Arabic Language Learning - Mardha Tilla; Wasilah; Enok Rohayati; Siska (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
This study aims to assess the effectiveness of the Jolly Phonics method in improving the maharah kitābah skills of students in the Arabic Language 1 class at Pondok Pesantren Al Qur’an Al Karim Palembang. Using a quasi-experimental design with data collected through pretests and posttests administered to 20 students, the results show that prior to the intervention, the students' maharah kitābah skills were categorized as moderate, with an average pretest score of 65.5. After the intervention, the average posttest score increased to 80.5, reflecting a 15% improvement. Hypothesis testing revealed a t-value of 4.016, which is greater than the t-table value of 1.711, thus confirming the acceptance of the alternative hypothesis (H_a) and rejection of the null hypothesis (H_o). The results of the Wilcoxon Signed Ranks Test indicated a significant difference between the pretest and posttest scores, with a Z-value of -3.193 and an Asymp. Sig. value of 0.001. This suggests that the observed changes in the students' scores were not coincidental but rather the result of the intervention. Overall, this study concludes that the Jolly Phonics method is effective in improving maharah kitābah skills in students.